If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 = 9x + -8x + 6 Reorder the terms: 5 = 6 + 9x + -8x Combine like terms: 9x + -8x = 1x 5 = 6 + 1x Solving 5 = 6 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 5 + -1x = 6 + 1x + -1x Combine like terms: 1x + -1x = 0 5 + -1x = 6 + 0 5 + -1x = 6 Add '-5' to each side of the equation. 5 + -5 + -1x = 6 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 6 + -5 -1x = 6 + -5 Combine like terms: 6 + -5 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1
| (7-x)(x^2+2x-3)=0 | | 6(6-4)=12y | | x+27=-52 | | x^2=128-8x | | 11x^2+2x=10 | | (7a^2-2a+6)-(-5a^2+3)=0 | | 3x+8(x-1)=0 | | -9.9-26.7=6.1-24.7r | | D^2+3d+4=0 | | 4x^2+7x+3=6 | | -9.9-26.7=6.1-24.7 | | (1.2x^5-5x^3-0.7)+(3.7x^5+3)=0 | | 2m^2-13m=0 | | 6overh=4 | | 8=6g-4 | | (x^2-4x-7)x(x^2-2x+5)= | | 22a=-a^2 | | y=5-x^2-x-9 | | (3x-5)*x=232 | | Ln(sin(x))= | | Y+3=2y^2 | | (7a^2-3a)-(5a^2-5a)=0 | | 3(x-21)+3(x-2)=27 | | (3x-5)*5=232 | | 2(x-5)=32x | | 15=10+5(x-4) | | 27x^2+8=0 | | x+35=-57 | | 14y-3y=6y+5 | | -.45+9t=-1.5+30t | | 4.8(0.6)= | | 5x-3(-1)=39 |